ANALYSIS OF SPA TOURIST MOTIVATIONS: A SEGMENTATION APPROACH BASED ON DISCRIMINANT ANALYSIS - Marcelino Sánchez-Rivero; Cristina Rodríguez-Rangel; Lidia Andrades-Caldito (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2016)
Changes in lifestyle and a growing awareness of the importance of health and quality of life are leading to a growing interest in health tourism in general and spa tourism in particular. For this reason, spa tourist motivations are changing and expanding, going from uni-motivational behaviours (cure an ailment or disease) to other that are clearly multimotivational (rest, relaxation, visit to cultural and natural destinations, enjoyment of food, etc.). The aim of this paper is to confirm the existence of a multi-motivational behaviour pattern in spa tourism as well as to quantify the percentage of the current demand showing this pattern. To do this, with the help of a discriminant analysis used to quantify the probability of the existence of several specific reasons for the practice of thermalism (search for rewarding emotions and feelings; improvement of health; relax; and improvement of physical condition), a segmentation of the demand of spa services in Extremadura (Spain) has been carried out. The results allow researchers to define three groups of tourists: the unmotivated, the multimotivated and the half-motivated. Multi-motivated tourists represent less than 14% of the total number of tourists, and show a high motivation to improve their physical condition and their health, as well as to simply relax in a spa resort. Consequently, although they still represent a small percentage of the market, multi-motivational behaviour in spa tourism is regarded as an emerging segment that will change both the future of spa resorts offer and the way in which customer demands are managed.